1974
DOI: 10.1021/i260052a013
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of Aqueous Gas Mixtures at Advanced Pressures

Abstract: A modified form of the Redlich-Kwong equation is used to obtain an approximate representation of the volumetric properties of gaseous water. Upon splitting the attraction constant a into a temperatureindependent dispersion-force term and a temperature-dependent dipole term, physically reasonable mixing rules are proposed for mixtures of water and nonpolar gases. Special attention is given to mixtures of water with carbon dioxide. The equation of state presented here does not yield high accuracy but provides go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 5 publications
0
34
0
Order By: Relevance
“…The densities of fluid inclusions can be used to put limits on these kinds of selective leakage. For example, calculations using the modified Redlich-Kwong equation of state of de Santis, Breedveld & Prausnitz (1974) and constants given by Holloway (1977) indicate that a mixed H,O-CO, fluid inclusion with 50mol. % H,O trapped at 750°C and 7 kbar would have a molar volume of 32.1 cm3/mol.…”
Section: The Inclusions Contain a C0-rich Fluid Left Behind After Thmentioning
confidence: 99%
“…The densities of fluid inclusions can be used to put limits on these kinds of selective leakage. For example, calculations using the modified Redlich-Kwong equation of state of de Santis, Breedveld & Prausnitz (1974) and constants given by Holloway (1977) indicate that a mixed H,O-CO, fluid inclusion with 50mol. % H,O trapped at 750°C and 7 kbar would have a molar volume of 32.1 cm3/mol.…”
Section: The Inclusions Contain a C0-rich Fluid Left Behind After Thmentioning
confidence: 99%
“…The temperature-dependent parameter, a ii 1 , is zero for gaseous oxygen. For water vapor, a ii 1 was taken from de Santis et al [4]. Because the modified RK EOS has not been verified yet for the oxygen-water system, it was investigated in the following text.…”
Section: Thermodynamic Modelmentioning
confidence: 99%
“…Fugacity coefficients of the components in the vapor phase were calculated with the modified Redlich-Kwong (RK) EOS [4]. The dissolved oxygen in the liquid phase followed Henry's law.…”
Section: Introductionmentioning
confidence: 99%
“…In the present deThat is, the deviations between calculated and experimental values for (z-1)v have been minimized. Then, the second and third virial coefficient data12) are adopted to fit more precisely (1) and (6) to (8) according to the thermodynamic standard procedure.…”
Section: Equation Of Statementioning
confidence: 99%
“…De Santis et al 1) have shown that the RedlichKwong equation of state is useful to correlate the solubility of water in compressed n-butane gas by adjusting the constant a reflecting the intermolecular attraction. De Santis and Marrelli2) have adopted a perturbed-hard-sphere equation of state (the repulsion term is given by Carnahan and Starling's expression3) and the attraction term is approximated by that of the Redlich-Kwong equation of state) to correlate the solubility of water in compressed air.…”
Section: Introductionmentioning
confidence: 99%